Zika Virus: A Current Public Health Challenge in India: A current public health challenge in India - Bhutia, Sonam Yangchen (International Journal of Innovative Research in Medical Science, 2018)
Zika virus disease (ZiV), a mosquito borne re-emerging disease in India transmitted by a vector aedes with an agent flavivirus in Brazil 2015 has spread to various parts of the countries where WHO has declared it as a global health concern. India with a favourable climate and geographical location with increase distribution of aedes species can result into increase outbreak of Zika virus diseases along with malaria, japanese encephalitis, chikungunya, dengue and scrub typhus in the future. This review states on current global incidence of Zika, epidemiology, mode of transmission, clinical manifestations, complications, diagnosis, treatment and its preventive measures and the threats and challenges of Zika virus disease in India.